FEMALE CUSTOMERS FOMO:THE ROLE OF THREATS AND CAPABILITIES TOWARDS CO-CREATION OF PROTECTION IN ONLINE BANKING SERVICES - Kusuma Ningtyas, Adisty; Sutarso, Yudi (Universitas Islam Lamongan, 2025)
This study aims to examine the effect of threat assessment and coping ability on the co-creation behavior of female customers in using digital banking services, with FOMO as a moderating variable. This study uses a survey research design, where data is collected through questionnaires distributed to female customers who use online banking from big cities in Indonesia. They are at least 17 years old, have used digital banking services for more than a year, and make transactions regularly. The results of the study indicate that threat assessment and coping ability have a positive effect on co-creation behavior. The ability to cope with risks also strengthens the involvement of female customers in joint protection. Meanwhile, FOMO is confirmed to moderate the relationship between threat assessment and co-creation behavior, but does not moderate the relationship between coping ability and the behavior. These findings emphasize the importance of the role of threat perception, digital literacy, and banking technology innovation in creating a safer and more trusted digital banking ecosystem